Campaign 'Fill My Plate' in Increasing Knowledge and Habituation of Balanced Nutrition Patterns Among Students of SIT An Nahl Percikan Iman Jambi: Kampanye ‘Isi Piringku’ Dalam Meningkatkan Pengetahuan dan Pembiasaan Pola Gizi Seimbang Pada Siswa Sit An Nahl Percikan Iman Jambi - Sofiyetti, Sofiyetti; Rusdi, Mesa Sukmadani (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
This community service project is titled "Fill My Plate Campaign: Increasing Knowledge and Habituation of Balanced Nutrition Patterns Among Students of SIT An Nahl Percikan Iman Jambi." The activities involved the school, including class teachers and health teachers, targeting a total of 60 students. The implementation of this community service, following the PKM scheme, was conducted over four days, from preparation to evaluation. The results of this community service activity include an increase in students' knowledge and habituation of balanced nutrition patterns, as well as the successful delivery of education on balanced nutrition through the "Fill My Plate" campaign method. This involved several activities, including the installation of posters in classrooms and the health room, distribution of flyers about "Fill My Plate," a booklet containing "Fill My Plate" guidelines and a 10-day meal cycle, presentation of materials accompanied by video screenings and the use of plate-shaped media, as well as discussions held at SDIT An Nahl Percikan Iman Jambi. Abstrak Pengabdian kepada masyarakat ini berjudul kampanye ‘isi piringku’ dalam meningkatkan pengetahuan dan pembiasaan pola gizi seimbang pada siswa Sit An Nahl Percikan Iman Jambi. Kegiatan ini melibatkan pihak Sekolah yaitu Guru Kelas dan Guru UKS dan siswa siswi sebagai sasaran sebanyak 60 orang. Pelaksanaan pengabmas dengan skema PKM dilakukan selama 3 (empat) hari mulai dari persiapan hingga evaluasi. Hasil Kegiatan pengabmas ini adalah peningkatan pengetahuan pengetahuan dan dan pembiasaan pola gizi seimbang siswa serta terlaksananya edukasi tentang gizi seimbang dengan metode kampanye isi piringku dengan beberapa tahapan kegiatan antara lain pemasangan poster di kelas dan ruang UKS, pemberian flyer tentang isi piringku, Booklet tentang isi piringku dan menu siklus 10 hari, pemaparan materi disertai pemutaran video dan media wadah piring makanku, serta diskusi yang dilakukan di SDIT An Nahl Percikan Iman Jambi.